Estudio de la correlación hidráulica y la remoción de contaminantes en agua residual sintética mediante un lecho filtrante de musa paradisiaca - Aucancela Rivera, Elvis Gribaldo (2018)
The objective of this work was to treat synthetic wastewater using the BRL blue dye of high, medium and low color concentrations with characteristics similar to that of a textile industry, to determine the correlation between flow velocity, permeability and removal of Cr +6, Cu, COD and color using filter bed of musa paradisiaca. Establishing treatability tests of 180 minutes for each concentration using 4 different permeabilities and applying to each of them 3 different flow velocities. From the results obtained, it was determined that the variables flow velocity and permeability are correlated with color removal, COD and Cr+6. Thus for the variable permeability the correlation is inversely proportional. For speed the color and COD the correlation is directly proportional and inversely proportional for the Cr+6. The best treatment was using fiber of 1 centimeter and high flow velocity in which 77.92% and 70.01% were removed for color and COD respectively. For Cr+6 the best treatment was fiber at 1 centimeter and low flow velocity removing up to 80% the concentration of this pollutant and for Cu the best treatment was fiber at three centimeter and low flow rate stirring up to 88.69%. Proving that the filter bed of musa paradisiaca is effective for the removal of these pollutants.